Longitudinal study of irradiation-induced brain functional network alterations in patients with nasopharyngeal carcinoma. (August 2022) - Fu, Gui; Xie, Yuanyao; Pan, Jie; Qiu, Yingwei; He, Haoqiang; Li, Zhipeng; Li, Jing; Feng, Yanqiu; Lv, Xiaofei
Highlights: Resting-state fMRI detected early radiation-induced brain functional abnormalities. Brain nodal changes were dynamic, mainly manifesting an 'impairment-recovery' pattern. D 20cc was an important prognostic determinant for nodal changes of STG.R. Abstract: Background: To investigate radiotherapy (RT)-related brain network changes in patients with nasopharyngeal carcinoma (NPC) over time and develop least absolute shrinkage and selection operator (LASSO)-based multivariable normal tissue complication probability (NTCP) models to predict RT-related brain network changes. Methods: 36 NPC patients were followed up at four timepoints: baseline, within 3 months (acute), 6 months (subacute), and 12 months (delayed) post-RT. 15 comparable healthy controls (HCs) were finally included and followed up in parallel. Functional neuroimaging data, dose–volume parameters of bilateral temporal lobes and Montreal Cognitive Assessment (MoCA) were acquired. Graph theoretical analysis and mixed-design analysis of variance were performed to investigate how the brain global and nodal changes were affected by RT. Multivariate logistic regression NTCP models were developed. LASSO with nested cross-validation strategy was used to select features. The relationships between network changes and MoCA changes were also examined. Results: Significant changes were detected in nodal efficiency (NE) in NPC patients but not in HCs over time. Altered NE was distributed in the bilateral frontal, temporal lobes and the right insula, which showed a "decrease-increase/recovery" pattern over time. Among all models, the model for predicting NE changes of STG.R showed a relatively good performance (area under the receiver operating curve: 0.68), and D 20cc and V 20 to right temporal lobe outperformed in this model. Conclusion: Our findings indicate that RT-induced brain injury begin at the acute period and follow a recovery over time. Furthermore, our study presents prediction models for brain dysfunction based on the dosimetric and clinical parameters.